2018
DOI: 10.3389/fphar.2018.00229
|View full text |Cite
|
Sign up to set email alerts
|

The Cytochrome P450-Mediated Metabolism Alternation of Four Effective Lignans From Schisandra chinensis in Carbon Tetrachloride-Intoxicated Rats and Patients With Advanced Hepatocellular Carcinoma

Abstract: It is highly valuable to study the pharmacokinetics of herbal components under the pathological condition of liver dysfunction for safe and rational use of herbal medicines. In this study, the pharmacokinetic profiles of four effective lignans from Schisandra chinensis (SC), schisandrin, schisantherin A, deoxyshisandrin and γ-schisandrin, were investigated in carbon tetrachloride (CCl4)-intoxicated rats. The metabolism of the four lignans was also studied using microsomes from patients with advanced hepatocell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…For example, Ho et al [ 80 ] reported potent inhibition of CYP1A2 by crampbark ( Virburnum opolus ) using a microplate-based assay of cDNA expressed CYP isoforms. Similarly, Schisandra chinensis has also been found to variably modify CYP isoforms [ 81 ]. Finally, Sheriffdeen et al [ 82 ] observed other traditional herbal medicines (not those found in e+ shot) inhibited CYP1A2-mediated metabolism of caffeine humans upon acute consumption of these herbs, most likely through competitive and/or non-competitive enzymatic inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ho et al [ 80 ] reported potent inhibition of CYP1A2 by crampbark ( Virburnum opolus ) using a microplate-based assay of cDNA expressed CYP isoforms. Similarly, Schisandra chinensis has also been found to variably modify CYP isoforms [ 81 ]. Finally, Sheriffdeen et al [ 82 ] observed other traditional herbal medicines (not those found in e+ shot) inhibited CYP1A2-mediated metabolism of caffeine humans upon acute consumption of these herbs, most likely through competitive and/or non-competitive enzymatic inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that hydroxylation and dehydrogenation mediated by Cytochrome P450 (CYP450) enzymes, especially CYP3A4, were the major metabolic pathways of cinobufotalin in vitro and in vivo (Han et al, 2016). Hence the activity reduction of multiple CYP450 isoenzymes in the HCC rat models (Peng and Ding, 2015; Wu R. et al, 2018) should lead to slower clearance rate of cinobufotalin, showing lower k 10 . Because that k 10 is the elimination rate constant that depends on metabolism and excretion of the compounds or drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic clearance ( CL int ) of schisandrin A was obtained from re‐analysis of its depletion in HLM, while contribution of CYP3A enzymes ( f m,CYP3A = 0.76) was estimated from the percent of inhibition by ketoconazole 11 . CL int of schisantherin A 9 and schisandrol B 12 were also specified based on their metabolic pathways 11 .…”
Section: Methodsmentioning
confidence: 99%
“… Total CL int value was extracted from Zhang et al 9 and f m , CYP3A4 was estimated based on the extent of inhibition by ketoconazole 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation